Negotiating Gendered Leadership Positions within African Initiated Christian Churches in Amsterdam - Justice R.K.O. Kyei; Elizabeth N.M.K. Yalley; Emmanuel K.E. Antwi (African Journal of Gender and Religion (AJGR))
Our research contributes to the discussion of feminist theorists on how the dominance of women in religious communities is not reflected in leadership positions of women. With the case of African Initiated Christian Churches (AICCs) in Amsterdam, this study investigates the intersection of gender, citizenship, and religion. The concept of religious citizenship provides the analytical tool to examine women-men relationships within immigrant religious communities. The research focuses on gendered leadership within the AICCs in Amsterdam, to enquire into how women exercise leadership in spite of the challenges faced in the AICCs. Data are drawn from in-depth interviews, participant observation, and informal interviews in Amsterdam. This study concludes that women’s access to hierarchical positions is nuanced, as main-line Protestant churches are more flexible compared to Pentecostal/Charis-matic churches. We argue that some women are situated in de facto second-class religious citizenship positions in religious communities which undermine women’s search for equal opportunities as religious citizens. Some women, however, exercise agency to circumvent the structural constraints.